Advances in the treatment of hereditary transthyretin amyloidosis: A review - Morie A. Gertz; Michelle L. Mauermann; Martha Grogan; Teresa Coelho (Brain and Behavior, 2019)
Abstract Introduction Amyloid transthyretin amyloidosis (ATTR) is a progressive and often fatal disease caused by the buildup of mutated (hereditary ATTR [hATTR]; also known as ATTR variant [ATTRv]) or normal transthyretin (wild‐type ATTR) throughout the body. Two new therapies—inotersen, an antisense oligonucleotide therapy, and patisiran, an RNA interference therapy—received marketing authorization and represent a significant advance in the treatment of amyloidosis. Herein, we describe the clinical presentation of ATTR, commonly used procedures in its diagnosis, and current treatment landscape for ATTR, with a focus on hATTR. Methods A PubMed search from 2008 to September 2018 was conducted to review the literature on ATTR. Results Until recently, there have been few treatment options for polyneuropathy of hATTR. Inotersen and patisiran substantially reduce the amyloidogenic precursor protein transthyretin and have demonstrated efficacy in patients with early‐ and late‐stage disease and in slowing or improving neuropathy progression. In contrast, established therapies, such as liver transplantation, typically reserved for patients with early‐stage disease, and tafamidis, indicated for the treatment of early‐stage disease in Europe, or diflunisal, a nonsteroidal anti‐inflammatory drug that is used off‐label, are associated with side effects and/or unclear efficacy in certain patient populations. Thus, inotersen and patisiran are positioned to be the preferred therapeutic modalities. Conclusions Important differences between inotersen and patisiran, including formulation, dosing, requirements for premedications, and safety monitoring, require an understanding and knowledge of each treatment for informed decision making.